Dietary Patterns and Their Relationship With the Perceptions of Healthy Eating in European Adolescents: The HELENA Study. (17th November 2019) - Giménez-Legarre, Natalia; Santaliestra-Pasías, Alba M.; Beghin, Laurent; Dallongeville, Jean; de la O, Alejandro; Gilbert, Chantal; González-Gross, Marcela; De Henauw, Stefaan; Kafatos, Anthony; Kersting, Mathilde; Leclerq, Catherine; Manios, Yannis; et al.
Abstract: Objective : The aim of this study was to identify dietary patterns (DPs) in European adolescents and to examine the association between perceptions of healthy eating and the obtained DPs. Method: A multinational cross-sectional study was carried out in adolescents aged 12.5 to 17.5 years and 2, 027 (44.9% males) were considered for analysis. A self-reported questionnaire with information on food choices and preferences, including perceptions of healthy eating, and two 24-hour dietary recalls were used. Principal component analysis was used to obtain sex-specific DPs, and linear analyses of covariance were used to compare DPs according to perceptions of healthy eating. Results: Three and four DPs for boys and girls were obtained. In boys and girls, there were significant associations between some perceptions about healthy food and the Breakfast-DP ( p  < 0.05). In boys, Breakfast-DP and Healthy Beverage-DP were associated with the perception of the own diet as healthy ( p  < 0.05). Healthy Beverage-DP was associated with those disliking fruits and vegetables ( p  < 0.05). Girls considering the own diet as healthy were associated with Mediterranean-DP, Breakfast-DP, and Unhealthy Beverage and Meat-DP ( p  < 0.05). The perception of snacking as a necessary part of a healthy diet was associated with Breakfast-DP in both genders ( p  < 0.05). Conclusions: In European adolescents, perceptions of healthy eating were mainly associated with a DP characterized by foods consumed at breakfast. Future studies should further explore these findings in order to implement health promotion programs to improve healthy eating habits in adolescents.